THE TEACHING PROFESSION IS ALWAYS PROMISING - Mirzaev Otabek Husanovich (Web of Journals Publishing, 2025)
In today's dynamically developing world, the work of a teacher goes far beyond the formal familiarization of students with certain knowledge. Allowing students to understand the world around them and its laws, viewed through the prism of children's perception, should give rise to a student's interest in further search and stimulate the desire to learn. The formation of a true citizen teacher, the upbringing of a person who is aware of his responsibility to society and the state, is the primary task of a teacher.
Keywords: Objectives of the discipline, objectives of the discipline, educational process, professional training, theoretical knowledge, practical skills, competencies, pedagogical activity, skill development, critical thinking, independent work, educational standards, teaching methods, pedagogical practice.